2020
DOI: 10.3390/photonics7040101
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Sensitized No-Core Fiber Step-Index Distribution Sucrose Sensor

Abstract: By coating graphene oxide (GO) onto the surface no-core fiber (NCF), we designed a single-mode no-core single-mode (SNS) fiber Step-Index Distribution sucrose sensor. With wavelength demodulation and the beam propagation method (BPM), the sensor without a GO coating was studied in the low RI range of 1.33~1.389, and the high RI range of 1.389~1.4185. The experiments show that the RI sensitivity of the sensor respectively reaches 132.9 nm/RIU and 292.22 nm/RIU. Both the numerical simulation and the experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The non-linear change happens due to the nonlinearity of evanescent wave energy when interacting with the analyte medium [21]. However, there is an extremely small change that occurred at the 5 µm cladding thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-linear change happens due to the nonlinearity of evanescent wave energy when interacting with the analyte medium [21]. However, there is an extremely small change that occurred at the 5 µm cladding thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the curve nonlinearity, Xiao et al suggested an easy determination of sensor sensitivity by evaluating the changes in linear t [21]. Thus, Table 1 shows the sensitivity changes towards the cladding thickness determined from the slope of the linear t. It can be concluded that the cladding thickness extremely affects the sensitivity of the planar waveguide sensor.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it is possible to improve the sensing field of the sensor through these excellent properties. This research provides a novel method for us to detect sucrose solution [ 101 ].…”
Section: Progress Of Graphene Optical Fiber Biochemical Sensormentioning
confidence: 99%
“…( f ) The relationship between the characteristic wavelength and the refractive index of the coated and uncoated GO. Reproduced from [ 101 ] with permission of the Multidisciplinary Digital Publishing Institute.…”
Section: Figurementioning
confidence: 99%
“…Single mode-no-core-single mode (SNS) fiber has attracted interest in applications as a refractive index (RI) sensor [1][2][3]. The no-core fiber (NCF) that is sandwiched between the single mode fiber (SMF) plays an important role as a sensing region.…”
Section: Introductionmentioning
confidence: 99%